(untitled) - Gruber, Diann (Oxford, 1994)
This book consists of eight units of varying length, each with a central topic or theme. Each unit bigins with familiarization or sensitization activities. It develops students' writing ability at elementary level. It focuses on the ability to organize information in the writing of personal letters, descriptions and application forms.
Keywords: English language,English language,English language; Study and teaching,Textbooks for foreign speakers,Writing